Patriarchal Domination in Ernest Prakasa’s Imperfect – an Adaptation Study - Ariany Hendrayuwana; Esther Harijanti Kuntjara (Institute of Research and Community Outreach - Petra Christian University, 2021)
This study deals with the adaptation of an Indonesian novel entitled Imperfect (2019) by Meira Anastasia into a film with a similar title Imperfect (2019) by Ernest Prakarsa. Although there are differences between the novel and the film adaptation, they have similarities in terms of the main issue of women’s physical insecurities and their struggle for self-acceptance. Considering that aspect, this study aims to argue the persistent existence of patriarchal domination despite the differences in the storyline and characterization. The adaptation also bears similarities that indicate the issue of women's insecurities and struggle for acceptance. In this study, the theory of adaptation and patriarchal beauty standards are used as a tool to analyze the film adaptation. despite the adapters’ aim to raise the issue of women's physical insecurities and criticize the patriarchy’s standard of beauty, the film adaptation even indicates the persistence of patriarchal domination. Keyword: beauty standard, film adaptation, patriarchy, self-acceptance, women insecurities